Penegakan Hukum Tindak Pidana Koneksitas Dalam Kasus Korupsi Yang Dilakukan Oleh Oknum Militer - Herdeand, Riandy (Jurnal Sosial Humaniora Sigli, 2025)
Connectivity is a type of justice that can be carried out with special decisions and is held specifically. Connectivity can only occur if the elements of legal subjects participating in committing criminal acts are of different groups. Different groups mean that criminal acts are committed jointly by two different groups in the judicial domain, namely between civilians and members of the armed forces. The problems discussed in this research What are the procedures for handling criminal cases involving corruption cases? How is the law enforced for criminal offenses in cases of corruption committed by military personnel? Normative juridical research methods. In conclusion, the implementation of connected justice can occur due to the discovery by the investigative team that a criminal offense has occurred between two legal subjects with different judicial domains together. In the procedures for handling criminal cases, the connection of corruption cases starts from the formation of an investigative team, a file research team which functions to determine the relative competence of the competent court, the implementation of the investigation, and the prosecution process. In terms of law enforcement of criminal acts of connection in corruption cases committed by military personnel based on Article 18 Paragraph (1) letter b of Law Number 31 of 1999 concerning Eradication of Corruption Crimes as amended by Law Number 20 of 2001, then other than The principal punishment is imposed in the form of imprisonment and additional punishment in the form of a fine and payment of compensation money in an amount equal to the maximum amount of property obtained from the Corruption Crime. Keywords : Military, Connectivity, Corruption